Intervensi edukasi worksheet-flashcard untuk meningkatkan asupan protein dan perilaku pemberian makan pada balita (3-5 tahun): Studi Quasi-Eksperimental - Sari, Novi Puspita; Khatimah, Husnul; Nasruddin, Dedi; Syahruddin, Akmal Novrian (Poltekkes Kemenkes Aceh, 2025)
Background: Various government programs have been implemented to address stunting, but there is still a lack of interactive educational interventions based on worksheets and flashcards to stimulate protein intake and feeding behavior in toddlers, which is expected to reduce stunting rates.Objectives: To assess the effect of educational media using worksheets and flashcards on protein intake and feeding behavior in toddlers (3-5 years old) in the Simbang Community Health Center (Puskesmas) working area, Maros Regency.Methods: This study used a quasi-experimental design with a two-group pretest-posttest control design. The sample consisted of n = 50 mothers with children aged 3-5 years old, consisting of an intervention group (n = 25) and a control group (n = 25). The study was conducted for one month (July–August 2025). Data were processed using WHO-Antro 2005 and Nutrisurvey 2007. Statistical analysis used paired t-tests and Wilcoxon tests. Meanwhile, the difference or Δ post-pre scores between the two groups was analyzed using the Independent t-test and the Mann-Whitney test. Statistical significance was set at p<0,05.Results: The results of the study showed that the intervention provided was proven effective in improving several indicators of child growth and nutrition, namely ∆ BB/A = 0,06 (Intervention) vs -0,04 (Control) p=0,014, ∆ TB/A = -0,03 (Intervention) vs -0,08 (Control) p=0,031, ∆ Median Knowledge = 4,0 (Intervention) vs 3,0 (Control) p=0,003, ∆ Median Attitude = 10,0 (Intervention) vs 3,0 (Control) p=0,012, ∆ Median Protein = 16,1 gr (Intervention) vs 3,3 gr (Control), p=0,030 (In the Intervention group), p=0,033 (Between groups ∆). However, the intervention did not have a significant effect on increasing energy intake. P=0,062.Conclusion: This intervention is effective in improving child growth and nutrition.